2016
DOI: 10.1080/19368623.2016.1156042
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Meanings of Food in Different Chinese Societies: The Cases of Taiwan and Malaysia

Abstract: Existing literature sheds little light on how Chinese consumers in any two societies perceive and consume food. In this study, the food perceptions of Taiwanese and Malaysian Chinese consumers are compared using a projective technique. Using images collected by respondents, both conscious and tacit interpretations of food were obtained. Findings reveal that Taiwanese and Malaysian Chinese share similar, but not identical, food perceptions. In this study, food is interpreted from a triadic framework: utilitaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Prior researchers proposed a triadic framework, encompassing the utilitarian, hedonic, and social motives to food and eating ( Khoo-Lattimore et al, 2016 ). Eating alone is commonly associated with utilitarian motives as opposed to the social motives of communal eating ( Takeda and Melby, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior researchers proposed a triadic framework, encompassing the utilitarian, hedonic, and social motives to food and eating ( Khoo-Lattimore et al, 2016 ). Eating alone is commonly associated with utilitarian motives as opposed to the social motives of communal eating ( Takeda and Melby, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emphasis on sharing and communal eating is also found in Chinese communities outside of mainland China ( Yang et al, 2014 ). Prior research has revealed the underlying meanings of group dining and food sharing in a collectivist Chinese culture, which include a way to maintain and develop interpersonal relationship and to represent social status ( Khoo-Lattimore et al, 2016 ; Ma, 2015 ). Eating together also plays an important role in rituals, celebrations, and remembrances in Chinese culture ( Yang et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourists can enjoy new food at any time of the year, and revenue from food spending can provide alternatives to those seasonal tourism activities that depend on temperature and climate (Kivela and Crotts 2006). To understand this market, research has been carried out on such areas as travelers’ food preferences (e.g., Chang, Kivela, and Mak 2010; Khoo-Lattimore, Yang, and Lai, 2016; Ramkissoon and Nunkoo 2010; Sánchez-Cañizares and Castillo-Canalejo 2015), tourists’ satisfaction with culinary events and restaurants (Bowden and Dagger 2011; Bowden-Everson, Dagger, and Elliott 2013), and their motivation to consume local foods (Sánchez-Cañizares and Lopez-Guzman 2012; Chang, Kivela, and Mak 2010; Frash, DiPietro, and Smith 2015; Jacob, Boulbry, and Guéguen, 2017; Kim and Eves 2012; Lu and Gursoy, forthcoming). With the rise of the experience economy, researchers have also endeavored to understand consumption of local foods as an experience (Walls et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recognition of the significance of addressing the transparency of data collection and data analysis, the authors provided a detailed account of the hotels analyzed based on theoretical sampling, and further described in sufficient detail both the research method and the analysis methods (i.e., the structural qualitative content analysis and detailed structure analysis). For another example, Khoo-Lattimore et al (2016) compared the food perceptions of Taiwanese and Malaysian Chinese consumers using a projective technique, where respondents were instructed to collect images and then participate in a 90-min in-depth interview. The authors presented a thick description of the unique research technique they employed (a psychoanalytical tool called the Zaltman metaphor elicitation technique), respondents’ recruitment, a nine-step data collection method, as well as data analysis of the transcribed interview data.…”
Section: Methodsmentioning
confidence: 99%